2022
DOI: 10.1590/fst.12422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-irradiation on the physicochemical and functional properties of rice protein

Abstract: In this study, rice protein was used as raw material to explore the effects of γ-irradiation treatment doses (0, 0.5, 1, 2, 3, 5 kGy) on the physicochemical properties of rice protein (particle size, zeta potential, secondary structure, scanning electron microscope microstructure), surface hydrophobicity (H 0 ), thermal stability), functional properties (solubility, water and oil retention, emulsification) and sensory quality. The results show that when the γ-irradiation dose is 2 kGy, the average particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The high levels of pathogen reductions suggest that gamma radiation treatment can be utilized to mitigate Listeria contamination of post-harvest carrot and tomato. In a commodity such as rice grains, gamma radiation dose of < 5kGy had no significant effects on sensory quality of rice protein (Yao et al, 2022).…”
Section: Resultsmentioning
confidence: 95%
“…The high levels of pathogen reductions suggest that gamma radiation treatment can be utilized to mitigate Listeria contamination of post-harvest carrot and tomato. In a commodity such as rice grains, gamma radiation dose of < 5kGy had no significant effects on sensory quality of rice protein (Yao et al, 2022).…”
Section: Resultsmentioning
confidence: 95%
“…According to previous research by Yao et al . (2022) and Tattiyakul et al . (2012), as the alteration severity increased, there was a decrease in T o in pea flour.…”
Section: Resultsmentioning
confidence: 97%
“…For this reason, the amount of amylopectin would decrease and the degree of crystallinity in the starch granules would also reduce (Liu et al, 2012). According to previous research by Yao et al (2022) and Tattiyakul et al (2012), as the alteration severity increased, there was a decrease in T o in pea flour. The data presented above demonstrated that the spatial structure of the protein and the intermolecular forces are altered by gamma-irradiation.…”
Section: Solubility Of Gamma-irradiated Tapioca Rice and Pea Flourmentioning
confidence: 94%
“…Different food raw materials have to adopt different levels of irradiation dose to retain freshness (Prakash, 2016;Rahman et al, 2018). A dose of 2-10 kGy is recommended for aquatic products and meat products to ensure the shelf life of the food and not to affect its nutritional properties (Yao et al, 2022). Badr (2012) studiedγ-ray irradiation and found that under a dose of 3 kGy, the edible safety of smoked salmon significantly increases without obvious influences on moisture content, salt, pH, total volatile base-nitrogen (TVB-N), and trimethylamine.…”
Section: Effects Of Cobalt-sourced γ-Irradiation On the Meat Quality ...mentioning
confidence: 99%